Intertextual transformations of Molière in the works of Ranko Marinković - Hansen-Kokoruš, Renate (Molière u hrvatskoj kulturi, 2024)
This article examines the influence of the French comic playwright Molière on the work of the Croatian author Ranko Marinković. Both in his prose and in his plays, Ranko Marinković implemented different techniques of intertextuality which were fundamental for the development of his own poetics. Molière’s plays Tartuffe, Don Juan, The Imaginary Invalid and The Miser have all been, amongst others, important sources for his literary work, including his critical essays. The article discusses both typological and referential modes of intertextuality and analyses in which ways Marinković appropriated Molièrian intertexts for the creation of meaning in his own texts. Specific attention is paid to the relationship between character development and plot conception, ie. the criticism of certain protagonists and their negative character traits, the technique of contrariness, social criticism, as well as the semantization of genres and meta discursivity.